Projeto ABC Pirambu em foco: avaliação da política de cogestão do Governo do Estado do Ceará - Moreira, Angela Maria Ferreira (2010)
This work is a report of the evaluation results of the co-management politic of the Ceará state government, having as end of the study, the actions developed by the ABC Project – Pirambu, on 2009. The poverty effects in the suburbs of Fortaleza took the Public Power to have wider actions in order to minimize the negatives results of that problematic situation, adopting a partnership with the civil society. Ceará state government, through the Secretary of Work and Social Development (STDS), in association with civil society organizations, representatives of the communities and Fortaleza suburbs, in a co-management system, went after the participation and the shared responsibility, for the solution of the problems lived by the community, implementing the ABC Project in 18 crucial points of the Fortaleza suburbs, looking for serving children and youth, ranging from 6 to 17 years old, that were on a risk situation and social vulnerability. For the present research was chosen the project located on the Pirambu suburb. The objective of the ABC Project is to contribute with social actions through sports, art, leisure and culture. It looks forward to take off the children out of the streets, providing education and abilities development, so they can prepare themselves to get into the labor market and coexist harmoniously in the society. The choose of this research was due to the involvement of the researcher, as a state social servant in the work of counseling of the popular movement on the Pirambu suburb, for twelve (12) years, while in the management of the Communitarian Center Luiza Távora-Pirambu, linked to the Secretary of Work and Social Development (STDS), of Ceará state. The survey results show that 88% of the Project ABC participants recognize that it was driver of their stocks, however it was detected fault in advising compromising effective communication between representatives of the CCCR and technicians STDS. It was found a high rate of poverty, yet there is a consistent work with families for lack of professionals. There is a very low participation in groups or forms of association, and the knowledge management system, only 2% of students, eight monitors and 7.3% of the representatives of the families know that the management system is the co-management. It‟s presented, hence, a reflexion about the scope and boundaries of the co-management politic, starting from the research result that analyzed the management as a whole, making it by the voice of the involved actors, and by of the meaning of the participants perceptions.